Effect of a Hedonic Stimulus on the Sleep Architecture of Male Wistar Rats - Peña-Escudero, Carolina; Priego-Fernández, Sergio; Caba, Mario; Rodríguez-Alba, Juan Carlos; Corona-Morales, Aleph Alejandro; García-García, Fabio (Sleep Science, 2023)
Objective Nocturnal animals forage and eat during the night and sleep during the day. When food is available only for a short period during the day, animals develop a catabolic state and exhibit locomotor behavior before accessing food, termed food anticipatory activity. Consequently, there is a disruption in the sleep pattern. The present study aimed to explore how anticipatory arousal emerges under circadian exposure to a palatable meal (PM) and disrupts sleep architecture.Materials and Methods Adult male Wistar rats were implanted with electrodes for continuous sleep recording and housed under a light/dark 12/12-hour cycle with free access to food and water. After basal recordings, the rats had access to a PM during the light period for eight days.Results The anticipatory arousal started on the third day. On the eighth day, we found an increase in wake time and a decrease in the non-rapid eye movement sleep (NREMS) and rapid eye movement sleep (REMS) times 45 minutes before the PM compared with the basal recordings. The REMS transitions (events from NREMS to REMS) showed a significant reduction during the light period of the eighth day of PM. In contrast, the number of NREMS transitions (events from wakefulness to NREMS) remained unchanged.Conclusion The results suggest that palatable food induces a motivational timing that leads the rat to wake by altering the sleep quota.
Keywords: anticipatory locomotor behavior; circadian entrainment; palatable meal; sleep